Análise da potência muscular de atletas de futebol da categoria juniores em diferentes momentos da temporada de competição - da Silva, J. F.; Dell'Antonio, E.; Netto, A. S.; de Lucas, R. D.; Cetolin, T.; Guglielmo, L. G. A. (Revista Brasileira de Ciência e Movimento, 2013)
The aim of this study was to compare the muscle power of the lower limbs by measuring the counter movement jump (CMJ) of soccer players at different moments of the season (end of the season, beginning and end of the next preseason). Body composition data were also collected at the three moments analyzed. Seventeen junior soccer players aged 17.8 ± 1.1 years from a professional football club participating in the Brazilian Championship volunteered to take part in this study. The % of body fat at the beginning of the preseason was significantly higher than that measured at the end of the previous season (p<0.05). Vertical jump height declined significantly (5.8%, p<0.05) after the completion of the preseason. On the other hand, muscle power was maintained at the three moments when normalized for body mass, suggesting that CMJ performance presents no modification after a short period (4 weeks) without formal training. Further, the large emphasis on aerobic